Efektivitas Pelaksanaan Terapi Empati terhadap Kemampuan Manejemen Konflik Perawat Pelaksana di RSUD H. Hanafie Muara Bungo tahun 2019 - Dewi Marlina; Yulastri Arif; Mira Susanti (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Conflict is an interaction process that results from a mismatch, disagreement and mismatch between two or more parties. There were 52 cases of conflict in the H. Hanafie Hospital that occurred between nurses in the inpatient room with various triggers, such as differences in income, misunderstandings, feeling less valued, feeling lack of tolerance and indiscipline. This study aims to analyze the effectiveness of the implementation of empathy therapy on the conflict management abilities of nurses in RSUD H. Hanafie Muara Bungo. This type of research is quantitative using the research design "Quasy Experimental Pre-Post Test With Control Group. The population in this study were all nurses in the inpatient room of the Hanafie Muara Bungo Regional Hospital with a total of 129 people. The sample of implementing nurses was 34 respondents. Sampling with simple random sampling. The results of the study there was a significant effect of the implementation of empathy therapy on knowledge (p = 0.002), attitude (p = 0.004) and skills (p = 0.008). It is hoped that the nurses will both avoid conflict, be willing to pay attention to the opinions and interests of others and resolve conflicts without harming other parties.